2020
DOI: 10.15252/embj.2020105479
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Irs2 by let‐7 mi RNA s is essential for homeostasis of the telencephalic neuroepithelium

Abstract: Structural integrity and cellular homeostasis of the embryonic stem cell niche are critical for normal tissue development. In the telencephalic neuroepithelium, this is controlled in part by cell adhesion molecules and regulators of progenitor cell lineage, but the specific orchestration of these processes remains unknown. Here, we studied the role of micro RNA s in the embryonic telencephalon as key regulators of gene expression. By using the early recombiner Rx‐Cre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 97 publications
(157 reference statements)
2
18
0
Order By: Relevance
“…However, miRNAs may persist long after DICER knockout begins, meaning that this manipulation may not effectively probe miRNA function in early progenitors. miRNA ablation at an earlier timepoint—using Rx-Cre-driven conditional knockout of DICER, which starts at E7.5—caused overt structural defects in the neuroepithelium by disrupting adherens junctions and inducing hyperproliferation of radial glial cells ( Fernández et al, 2020 ). Part of the above phenotype seem to be mediated by miR-302a-d, a member of a miRNA family highly implicated in regulating cell cycle in embryonic stem cells.…”
Section: Neurogenesis and Neuronal Fatementioning
confidence: 99%
“…However, miRNAs may persist long after DICER knockout begins, meaning that this manipulation may not effectively probe miRNA function in early progenitors. miRNA ablation at an earlier timepoint—using Rx-Cre-driven conditional knockout of DICER, which starts at E7.5—caused overt structural defects in the neuroepithelium by disrupting adherens junctions and inducing hyperproliferation of radial glial cells ( Fernández et al, 2020 ). Part of the above phenotype seem to be mediated by miR-302a-d, a member of a miRNA family highly implicated in regulating cell cycle in embryonic stem cells.…”
Section: Neurogenesis and Neuronal Fatementioning
confidence: 99%
“…Altogether, this study reveals the existence of key periods of development when neural progenitors are highly sensitive to miRNA dysregulation, possibly leading to the initiation of major brain pathologies. [ 68 ]…”
Section: Mirnas Control Brain Developmentmentioning
confidence: 99%
“…[ 88 ] In a recent study, our laboratory revealed that loss of let‐7 miRNAs in the early embryonic forebrain (by means of Rx ‐dependent conditional Dicer1 KO) upregulates multiple signaling pathways that promote cell proliferation and loss of apical cell adhesion, resulting in the critical loss of homeostasis of the telencephalic neuroepithelium. [ 68 ] Let‐7 miRNA synthesis is subject to post‐transcriptional mechanisms of regulation, controlling the accumulation of mature miRNAs. [ 89 ] One of these regulatory mechanisms is a double‐negative feedback loop between let‐7 and the pluripotency factor Lin28.…”
Section: Mirnas Regulate Brain Development In Space and Timementioning
confidence: 99%
See 1 more Smart Citation
“…IRS2 could also be regulated by ncRNAs, like miRNAs. For example, IRS2 is a direct target of let-7 miRNA, and let-7/IRS2 is essential for the telencephalic neuroepithelium 27 . Here, we identi ed that IRS2 is also a direct target of miR-7-5p.…”
Section: Discussionmentioning
confidence: 99%